The Impact of Frequency and Duration of Diving Activities on the Occurrence of Decompressive Sickness - Chabibah, Nur; Mayasari, Ayu Citra; Rachmawati, Dhian Satya; Mohd Said, Faridah Binti (The Malaysian Journal of Nursing (MJN), 2022)
Background: Diving activities have a risk of disease called decompression sickness. One of the risks for the incidence of decompression sickness is the number of hours of diving and diving experience. This study aims to analyze the number of dives in a week and the experience of diving on the occurrence of decompression sickness. Methods: The study used an observational analytic design with a cross-sectional approach, involving 66 divers as research samples taken by simple random sampling. Data were collected using questionnaires and observations of divers’ health status to see the incidence of decompression in divers. Data were analyzed using logistic regression with a significance value of P<0.05. Results: The results showed that the number of hours of diving in one week, and diving experience influenced the incidence of decompression sickness experienced by divers (p<0.05). The results of the regression test showed an Exp (B) value of 10,540 for the number of dives in a week, which means that the value of the number of dives in a week >10.5 hours tended to experience decompression compared to those with a number of dives <10.5 hours, and the Exp (B) value of 2,645 during the working period of a long dive. This means that diving experience of >2.6 years are more likely to experience decompression compared to those with experience <2.6 years. Conclusion: Monitoring diving activities and the complaints felt by divers after diving is needed as early detection of decompression sickness, providing appropriate activities, and reducing the impact of decompression sickness on divers.